Agricola and the Antonine Wall - Haverfield, Professor (Proceedings of the Society of Antiquaries of Scotland, 1918)
Excavations intended to explore the Antonine Wall and its defending forts built by the Emperor Pius, about A.D. 140-145 demonstrated early on that that some, at least, of the forts of Pius stood on sites which had been fortified by Agricola sixty years earlier. Evidence from the forts at Barhill, Rough Castle, Camelon, Castle Cary and Cadder is considered.